The Significance Of Work Ethics İn Human Resource Management For Upgrading The Performance Of Employees: An Applied Study - Mathani, Belal A. (European Scientific Journal, ESJ, 2016)
This study was aimed at learning about the reality of work ethics practices in human resource management. This work was performed in conjunction with organizations that are affiliated with public services, such as Greater Irbid Municipality. It measured their effectiveness in raising the standard of performance. Additionally, the aim of the study is to identify the most important fields of application of work ethics in human resource management (attracting human resources, training and development, remuneration and rewards, and evaluating employees). The study begins with addressing the problem through the aforementioned main premise. However, there was no statistically significant impact at a=0.05 level of significance for work ethics practices in human resource management to improve the performance of the workers of Greater Irbid Municipality. Following up the descriptive analytical method, the study has shown that there is a statistically significant relationship between the dimensions of work ethics practices in human resource management in improving the performance of Greater Irbid Municipality. The sample of the study was made up of a population of 350 employees of Greater Irbid Municipality, who were selected by random method. The study analyzes the aforementioned items under two hypothetical theories using the well-known six statistical methods. The methods showed that the samples fell in a range greater than 0.05 ≥ α which were proven to be within a normal distribution. Additionally, the linear correlation test showed that the inflation coefficient of variation (VIF) is ranged between 2.22 and 4.30, while the Tolerance value for all independent variables greater than 0.05 ranged between 0.23 and 0.45. Therefore, it can be said that there is no high correlation problem between independent variables. This enhances the possibility of finding out which of the independent variables have a statistically significant impact on development variables, as well as to know the percentage of that impact factor. Furthermore, the methods showed the correlation between dependent and independent variable, giving a value greater than 0.77 and an R-square value of 0.58. This is statistically significant, which reveals the effectiveness of work ethics of human resource management in influencing the performance level.